Academicianul Valeriu RUDIC – savant, microbiolog şi inventator remarcabil - OH&RM, Consiliul Editorial (One Health & Risk Management, 2022)
Born on February 18, 1947 in the village of Talmaza, Ştefan Vodă district, after graduating from high school, he was admitted to the State Institute of Medicine in Chisinau, to the Faculty of General Medicine, which he graduated with honors in 1971. The future academician Valeriu Rudic and - began the path to glory in the Department of Microbiology, Virology and Immunology, being admitted to the doctorate. In the early 70’s the young doctoral student had the courage to study a problem of great value even today - cholera, conducting investigations not only on saprophytic strains, but also on pathogenic cultures. As a result of many researches, experiments, researches and analyzes, a new, complex and rapid method of diagnosing cholera was developed, which was successfully confirmed and approved on pathogenic strains of classical vibrios and el-tor in the town. Stavropol, at the Union Station for Scientific Research in the Field of Extremely Dangerous Infections. With an enviable ability to work, he completed the volume of pre-term investigations and in 1974 successfully defended his doctoral dissertation.